A comparative review of the resistance of a 37,000 dwt Chemical Tanker based on experimental tests and calculations - Crudu, Liviu; Bosoancă, Radu; Obreja, Dan (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
The evaluation of ship resistance is of paramount importance having a decisive impact on the economic performances and efficiency depending on mission. If new IMO requirements through the Energy Efficiency Design Index (EEDI) are taken into account the necessity to have more and more accurate tools capable to consider the influences of different parameters became mandatory. The availability of towing tank facilities and the full scale trials are the practical means in order to be able to confirm the accuracy of theoretical formulations and to define the limits of CFD applications. Based on the results of the towing tank tests, a direct comparison with the results provided by classical methods and CFD computations can be systematically can be performed. On the other hand, the influences of the modifications operated on the fore part of the ship are theoretically evaluated and compared with the towing tank results. Consequently, the paper is focused on the comparison of the results evaluated using different tools which have been carried out for a Chemical Tanker built by Constanta Shipyard Romania.